Synergizing volunteered geographical information and Earth observation for enhanced disaster management - Li, Hao; Knoblauch, Steffen; Yan, Yingwei; Zipf, Alexander (Data-driven earth observation for disaster management, 2026)
Natural disasters play a key role in shaping human–urban infrastructure interactions and its climate resilience; an effective and efficient response to natural disasters is essential for building resilience and a sustainable urban environment. In the recent decades, the increasing availability of Earth observation (EO) data offers a promising data source for rapid disaster risk reduction. In addition, volunteered geographic information (VGI) data become population, especially in combination with multimodal EO data, in support of real-time and fine-grained disaster mapping at scale. In this context, this chapter investigates the synergy between EO and VGI data by identifying their key advantages and providing two case studies on how to jointly explore the VGI and EO data in diverse disaster response scenarios, ranging from OpenStreetMap missing built-up area mapping to cross-view geolocalization and disaster mapping. Last but not least, we discussed the future working direction to further leverage the advantage of VGI and EO data in a broader scope of disaster management.